Legal Implementation of the Provisions of Working Hours for Workers Who Receive Wages Under Umk (Case Study of Coffee Shops in Cirebon City) - Ahmad Rivaldi; Ifan Firman Maulid; Farridzky Salsabila; Harmono; Gusti Yosi Andri (Indonesian Journal of Business Analytics, 2025)
Labor's role and position in national development are crucial. Therefore, employment development aims to improve the quality of labor and its participation in development. In addition, employment development also aims to increase protection for workers and their families, in line with human dignity and as mandated by the 1945 Constitution Article 27, paragraph 2: Every citizen has the right to work and a livelihood that is worthy of humanity. This study aims to examine the enforcement of legislation concerning MSME workers, specifically on working hours and salaries, in alignment with existing laws and regulations, while taking into account the constraints encountered by business operators in adhering to government policies. Methods. The research employed is empirical. Normative research is an investigative methodology that integrates normative and empirical viewpoints. The research on three coffee shops in Cirebon reveals a common issue concerning salaries, specifically that workers receive compensation below the Regency/City Minimum Wage (UMK). These data suggest that several business owners encounter similar issues with the remuneration provided to their employees. This contradicts the pay regulations stipulated in the Labor Law (Law No. 13/2003). The study's results indicate that research on the MSME sector reveals persistent issues in applying labor legislation concerning wages. The primary impediment to enforcing legal protections for workers in MSMEs arises not from employers' errors or ignorance but from the prevailing wage standards.